2022
DOI: 10.1007/s10433-022-00710-5
|View full text |Cite
|
Sign up to set email alerts
|

A link between age, affect, and predictions?

Abstract: The prevalence of depressive symptoms decreases from late adolescence to middle age adulthood. Furthermore, despite significant losses in motor and cognitive functioning, overall emotional well-being tends to increase with age, and a bias to positive information has been observed multiple times. Several causes have been discussed for this age-related development, such as improvement in emotion regulation, less regret, and higher socioeconomic status. Here, we explore a further explanation. Our minds host menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Despite these methodological limitations, the recent literature highlights the effects and risk variables for late life depression, although it Volume 6; Issue 01 Int J GeriatrGerontol, an open access journal ISSN: 2577-0748 doesn't conclude that aging is associated with more depression necessarily than other stages of life. Despite all the negative effects reported for aging and depression and the methodological limitations mentioned for this recent literature, at least one research group has suggested that the prevalence of depression has decreased with age [71]. The authors argue that this has related to a bias toward positive information, increased emotion regulation, less regret and greater socioeconomic status.…”
Section: Methodological Limitationsmentioning
confidence: 91%
“…Despite these methodological limitations, the recent literature highlights the effects and risk variables for late life depression, although it Volume 6; Issue 01 Int J GeriatrGerontol, an open access journal ISSN: 2577-0748 doesn't conclude that aging is associated with more depression necessarily than other stages of life. Despite all the negative effects reported for aging and depression and the methodological limitations mentioned for this recent literature, at least one research group has suggested that the prevalence of depression has decreased with age [71]. The authors argue that this has related to a bias toward positive information, increased emotion regulation, less regret and greater socioeconomic status.…”
Section: Methodological Limitationsmentioning
confidence: 91%
“…Existing literature has provided a wealth of evidence and theoretical explanations underlying the emotional powers of music through a Bayesian inference perspective (i.e., musical expectancy, probabilistic predictions and statistical learning). However, the scope of emotions and aging via a Bayesian inference perspective seems to be more focused on the phenomenon that older adults tend to prefer positive experiences over negative ones (see Lima & Castro, 2011;Trapp et al, 2022). This is also known as the positivity effect, which is beyond the scope of inquiry for this review.…”
Section: Emotions Cognition and Social Factors: Need For Integration ...mentioning
confidence: 99%